Interpretation of Spatial Language in a Map Navigation Task - Levit, Michael; Roy, Deb (Transactions on Systems, Man and Cybernetics, Transactions on Systems, Man and Cybernetics, Part B, 2007)
We have developed components of an automated system that understands and follows navigational instructions. The system has prior knowledge of the geometry and landmarks of specific maps. This knowledge is exploited to infer complex paths through maps based on natural language descriptions. The approach is based on an analysis of verbal commands in terms of elementary semantic units that are composed to generate a probability distribution over possible spatial paths in a map. An integration mechanism based on dynamic programming guides this language-to-path translation process, insuring that resulting paths satisfy continuity and smoothness criteria. In the current implementation, parsing of text into semantic units is performed manually. Composition and interpretation of semantic units into spatial paths is performed automatically. In evaluations, we show that the system accurately predicts speakers’ intended meanings for a range of instructions. This work provides building blocks for a complete system that, when combined with robust parsing technologies, could lead to a fully automatic spatial language interpretation system.